Precise measures of orbital period, before and after nova eruption for QZ Aurigae. Issue 1 (4th May 2019) - Schaefer, Bradley E; Boyd, David; Clayton, Geoffrey C; Frank, Juhan; Johnson, Christopher; Kemp, Jonathan; Pagnotta, Ashley; Patterson, Joseph O; Rodríguez Marco, Miguel; Xiao, Limin
ABSTRACT: For the ordinary classical nova QZ Aurigae (which erupted in 1964), we report 1317 magnitudes from 1912–2016, including four eclipses detected on archival photographic plates from long before the eruption. We have accurate and robust measures of the orbital period both pre-eruption and post-eruption, and we find that the orbital period decreased, with a fractional change of −290.71 ± 0.28 parts-per-million across the eruption, with the orbit necessarily getting smaller. Further, we find that the light curve outside of eclipses and eruption is flat at near B = 17.14 from 1912–1981, whereupon the average light curve starts fading down to B = 17.49 with large variability. QZ Aur is a robust counter-example against the Hibernation model for the evolution of cataclysmic variables, where the model requires that all novae have their period increase across eruptions. Large period decreases across eruptions can easily arise from mass imbalances in the ejecta, as are commonly seen in asymmetric nova shells.